2004
DOI: 10.1111/j.1469-8137.2004.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional constraints in ombrotrophic Sphagnum plants under increasing atmospheric nitrogen deposition in Europe

Abstract: Summary• We studied the effects of increasing levels of atmospheric nitrogen (N) deposition on nutrient limitation of ombrotrophic Sphagnum plants.• Fifteen mires in 11 European countries were selected across a natural gradient of bulk atmospheric N deposition from 0.1 to 2 g/m 2 year − 1 . Nutritional constraints were assessed based on nutrient ratios of N, phosphorus (P), and potassium (K) in Sphagnum plants collected in hummocks (i.e. relatively drier microhabitats) and in lawns (i.e. relatively wetter micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 56 publications
14
153
1
Order By: Relevance
“…At each study bog, litter peat samples were collected in similar plant communities and microtopographic positions (hummocks and lawns) as previously described (35). The sampling was performed in areas with a dense cover of healthy Sphagnum plants and a very sparse, if any, cover of vascular plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each study bog, litter peat samples were collected in similar plant communities and microtopographic positions (hummocks and lawns) as previously described (35). The sampling was performed in areas with a dense cover of healthy Sphagnum plants and a very sparse, if any, cover of vascular plants.…”
Section: Methodsmentioning
confidence: 99%
“…However, Sphagnum productivity has only been shown to respond positively to atmospheric N deposition until a critical threshold of Ϸ1 g of N⅐m Ϫ2 ⅐yr Ϫ1 , beyond which productivity is reported to decrease (30,(33)(34)(35). Moreover, increased N deposition may also give a competitive advantage to vascular plants (30,36) whose litter is more easily decomposed (37).…”
Section: Figmentioning
confidence: 99%
“…As the N:P ratios were already relatively high at the start of our experiment, with values of 25 or higher, this might indicate that Sphagnum was already P limited, since P limitation occurs at high N:P ratios ([15 according to Aerts et al 1992; [30 according to Bragazza et al 2004). Bragazza et al (2004) suggest that the critical load of N deposition in Europe is 1 g N m -2 year -1 , above which Sphagnum plants change from being N-limited to being P and K co-limited at N:P [ 30 and N:K [ 3. This would indicate that Sphagnum was P-limited in all treatments in our study and colimited by P and K in the high N treatment.…”
Section: Nitrogenmentioning
confidence: 97%
“…Atmospheric N deposition in Europe varies from 0.1 to 2 g N m -2 year -1 (Bragazza et al 2004), although higher values up to 5 g N m -2 year -1 are reported for the Netherlands (RIVM 2004). Our N addition of 4 g N m -2 year -1 is therefore already relatively high, but actual N availability might have been even higher because of nutrient mineralisation from the Sphagnum and peat in containers.…”
Section: Nitrogenmentioning
confidence: 99%
“…Peat mosses (Sphagnum spp.) function as a filter that very effectively absorbs particularly ammonium (NH + 4 ) but also nitrate (NO − 3 ) from atmospheric deposition, leading to N limitation in the rhizosphere of vascular plants (Lamers et al, 2000;Bragazza et al, 2004;Fritz et al, 2014). Since the availability of N determines primary production, there appears to be a close link between the N and C cycles (Hungate et al, 2003;Vitousek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%